A Study of the Bildungsroman in Charles Dickens’s David Copperfield - Wesal Muftah Ahmed Swi (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2025)
This paper examines Charles Dickens’ David Copperfield as a classic model of the Bildungsroman, a genre that traces the main character’s emotional and moral growth from childhood to adulthood through journey towards maturity. It is divided into two sections. The first one explains the notion of Bildungsroman, including its kinds, essential features, origins, and historical background. The second one examines the growth of main character, David Copperfield, from childhood to adulthood. It also explores significant traits of the Bildungsroman in his journey. It illustrates how David’s life embodies various features of the Bildungsroman, making him an excellent example of this genre.